Aquisição de habilidades motoras aquáticas: um programa de intervenção estruturado com base na teoria de instrução para crianças jovens - Teixeira, Clarice Alves (2008)
The study with experimental character investigated the influence of a structured intervention program based on the instruction theory for the acquisition of aquatic motor skills, in young children. Were subjects of the study 75 children enrolled in the public teaching network. As instruments were used: an identification chart for young children; perceived competence questionnaire; activities routine questionnaire; motor performance test (TGMD2); aquatic motor skills test (ARA) and the implementation of an intervention program based on Predisposition, Structure, Sequence and Reinforcement from Bruner (2006). Three groups were delineated for the motor intervention program: G1 experimental with 3 classes; G2 experimental with 2 classes and G3 (control group). The intervention occurred in 16 weeks. For the data analysis were used the tests: Interclass correlation, Mean and SD and relative frequency; paired t test; One Way nova, Post Hoc (Tukey HSD), General Linear Model (repeated measures), Wilk´s Lambda and categorical quantitative analysis. The results demonstrated: there were no significant gains in the motor quotient from G1 and G2 groups, however, for the locomotion skills significant gains were fond for the children from the intervention program, accepting partially the H1 hypothesis; the aquatic motor skills showed significant changes in the G1 and G2 groups, evidencing significant interactions in the time and groups factors, time factor and group effect, accepting the H2 hypothesis; as for general perceived competence, the G1 and G2 groups did not show significant changes, while G3 demonstrated a significant change in all the three times, rejecting the H3 hypothesis; as for the correlations, the results evidenced that there was a positive, moderate and significant correlation among the aquatic motor skill and total vast motor performance (r=0,387*); G1 presented a positive, moderate and significant correlation among the aquatic motor skill and total vast motor performance (r=0,460*); G2 did not show a correlation and G3 demonstrated a positive, moderate and significant correlation among the same variables (r=0,520*); the influence of the aquatic motor intervention program with different frequencies demonstrated significant changes in the aquatic motor skills acquisition in the groups (G1 and G2) when compared to G3, accepting the H4 hypothesis, however, there were no significant differences in the acquisition of aquatic motor skills between G1 and G2, rejecting the hypothesis H5. So I is concluded that: the intervention program structured with bases in the instruction theory for young children had a significant influence in the acquisition of aquatic motor skills, in the groups experimental G1 and G2.